A Loading Dose of Dexmedetomidine With Constant Infusion Inhibits Intraoperative Neuromonitoring During Thoracic Spinal Decompression Surgery: A Randomized Prospective Study - Liu, Tun; Qin, Yue; Qi, Huaguang; Luo, Zhenguo; Yan, Liang; Yu, Pengfei; Dong, Buhuai; Zhao, Songchuan; Wu, Xucai; Chang, Zhen; Liu, Zhian; Liu, Xuemei; et al. (Frontiers in Pharmacology, 2022)
Background: The effect of a bolus dose of dexmedetomidine on intraoperative neuromonitoring (IONM) parameters during spinal surgeries has been variably reported and remains a debated topic. Methods: A randomized, double-blinded, placebo-controlled study was performed to assess the effect of dexmedetomidine (1μg/kg in 10 minutes) followed by a constant infusion rate on IONM during thoracic spinal decompression surgery (TSDS). A total of 165 patients were enrolled and randomized into three groups. One group received propofol and remifentanil based total intravenous anesthesia (TIVA) (T group), one group received TIVA combined with dexmedetomidine at a constant infusion rate (0.5 μg kg-1 h-1) (D1 group), and one group received TIVA combined with dexmedetomidine delivered in a loading dose (1µg kg-1 in 10 minutes) followed by a constant infusion rate (0.5 μg kg-1 h-1) (D2 group). The IONM data recorded before test drug administration was defined as the baseline value. We aimed at comparing the parameters of IONM. Results: In the D2 group, within-group analysis showed suppressive effects on IONM parameters compared with baseline value after a bolus dose of dexmedetomidine. Furthermore, the D2 group also showed inhibitory effects on IONM recordings compared with both the D1 group and the T group. Including a statistically significant decrease in SSEP amplitude and MEP amplitude, and an increase in SSEP latency. No significance was found in IONM parameters between the T group and the D1 group. Conclusions: Dexmedetomidine delivered in a loading dose can significantly inhibit IONM parameters in TSDS. Special attention should be paid to the timing of a bolus dose of dexmedetomidine under IONM. However, dexmedetomidine delivered at a constant speed does not exert inhibitory effects on IONM data. Clinical Trial Registration: ChineseClinicalTrialRegistry.cn; Identifier: ChiCTR1800018685.